Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1021/cb500108p
|View full text |Cite
|
Sign up to set email alerts
|

Nav1.1 Modulation by a Novel Triazole Compound Attenuates Epileptic Seizures in Rodents

Abstract: Here, we report the discovery of a novel anticonvulsant drug with a molecular organization based on the unique scaffold of rufinamide, an anti-epileptic compound used in a clinical setting to treat severe epilepsy disorders such as Lennox-Gastaut syndrome. Although accumulating evidence supports a working mechanism through voltage-gated sodium (Nav) channels, we found that a clinically relevant rufinamide concentration inhibits human (h)Nav1.1 activation, a distinct working mechanism among anticonvulsants and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 62 publications
0
34
0
Order By: Relevance
“…Moreover, Na v 1.1 expression in other regions of the brain may contribute to Hm1a toxicity (4). Nonetheless, our Na v 1.1 inactivation gating model provides a rationale for developing new Na v 1.1-selective agents with a greater safety margin (11). For example, a VSDIV-binding compound that equally favors the resting and activated voltage sensor over a subsequent slowinactivation-coupled state should prevent Na v 1.1 accumulation in the slow inactivated state without introducing persistent current.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Na v 1.1 expression in other regions of the brain may contribute to Hm1a toxicity (4). Nonetheless, our Na v 1.1 inactivation gating model provides a rationale for developing new Na v 1.1-selective agents with a greater safety margin (11). For example, a VSDIV-binding compound that equally favors the resting and activated voltage sensor over a subsequent slowinactivation-coupled state should prevent Na v 1.1 accumulation in the slow inactivated state without introducing persistent current.…”
Section: Resultsmentioning
confidence: 99%
“…Human Na v 1.1 was obtained from Origene Technologies and modified as reported previously (11). Rat Na v 1.4 was a gift from Baron Chanda, University of Wisconsin-Madison.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each mouse was manually restrained during corneal stimulation (6 Hz, 0.2-ms pulse, 3 s) using a constant current device (ECT Unit 57800; Ugo Basile, Comerio, Italy). Behavioral seizures were scored based on a modified Racine Scale (RS): RS0 = no abnormal behavior; RS1 = immobile for ≥3 s, then resumption of normal behavior; RS2 = forelimb clonus, paw waving; RS3 = generalized tonic-clonic seizure with rearing and falling 31 . Male mice were tested at three current intensities: 18 mA ( N = 11–16/group), 22 mA ( N = 16–22/group), and 27 mA ( N = 16–22/group) with a one-week recovery between each test session.…”
Section: Methodsmentioning
confidence: 99%
“…9 It was reported that triazole compounds exhibited kinds of pharmacological abilities, such as anti-inflammatory, analgesic, antinociceptive, antiepileptic etc. [10][11][12][13][14][15][16] 1,2,3-Triazole and 1,2,4-triazole all possess anti-inflammatory activity. [11][12][13]16 In order to search new compounds with higher anti-inflammatory activities and lower toxicity, 1,2,3-triazole and 1,2,4-triazole derivatives were designed on the basis of association principle.…”
Section: Introductionmentioning
confidence: 99%